2004
DOI: 10.1124/jpet.104.075150
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Communication (“Quorum Sensing”) via Ligands and Receptors: A Novel Pharmacologic Target for the Design of Antibiotic Drugs

Abstract: The purpose of the present Perspectives is to present a synopsis of the literature on bacterial "quorum sensing" as a background for the proposal that interference with this communication system offers potential targets for the design of novel antibiotic drugs. Quorum sensing is the recently discovered chemical communication system among bacteria (both Grampositive and -negative). It is vital for intra-and interbacterial gene regulation and for keeping bacterial colonies ("biofilms") intact, allowing resident … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(68 citation statements)
references
References 48 publications
1
65
0
1
Order By: Relevance
“…Halogenated furanones, a new kind of antibacterial agent, posses stable antimicrobial activity against a great number of bacteria, 19 while less prone to resistance development. 20 Because BBF was one of the most active halogenated furanone compounds, 29 it was used in this study. To achieve the goal of sustained release, BBF was incorporated into PLLA-NPs, and then we developed a method to fabricate a new antibacterial coating, by cross-linking the BBF/ PLLA-NPs on MAO Ti.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Halogenated furanones, a new kind of antibacterial agent, posses stable antimicrobial activity against a great number of bacteria, 19 while less prone to resistance development. 20 Because BBF was one of the most active halogenated furanone compounds, 29 it was used in this study. To achieve the goal of sustained release, BBF was incorporated into PLLA-NPs, and then we developed a method to fabricate a new antibacterial coating, by cross-linking the BBF/ PLLA-NPs on MAO Ti.…”
Section: Discussionmentioning
confidence: 99%
“…19 Therefore, halogenated furanones acting as N-acyl homoserine lactone antagonists inhibit microbial colonization, and the antimicrobial mechanism would render halogenated furanones less prone to the development of drug resistance. 20 Moreover, studies have indicated that halogenated furanones possess excellent biocompatibility. 21 Based on these advantages, we have developed a new antibacterial coating containing a halogenated furanone compound, (Z-)-4-Bromo-5-(bromomethylene)-2(5H)-furanone (BBF)-loaded poly(l-lactic acid) (PLLA) nanoparticles (BBF-PLLA-NPs) on microarc-oxidized (MAO) Ti in our previous study.…”
mentioning
confidence: 99%
“…Furthermore, loss of agr activity has been linked to resistance to methicillin and vancomycin indicating a kind of compensatory mechanism between loss of virulence and resistance (Balaban et al, 1998;Raffa et al, 2005). Similarly, studies carried out in MRSA with type II SCCmec type have been shown to have decreased expression of cytolytic toxins as compared to MRSA with type IV SCCmec (Stewart et al, 2001).…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%
“…In addition, studies have also revealed the relationship between persistent bacteraemia and resistance to methicillin (Raffa et al, 2005). Furthermore, loss of agr activity has been linked to resistance to methicillin and vancomycin indicating a kind of compensatory mechanism between loss of virulence and resistance (Balaban et al, 1998;Raffa et al, 2005).…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%
“…23 The novel nature of their mechanisms of action would allow these new antimicrobials to be effective against bacteria that are currently antibiotic-resistant. 24 In spite of the inhibitory effects on microbial biofilm formation, reports of the effects on eukaryotic cell viability and toxicity of halogenated furanone compounds are scarce, and reports on genotoxic effects seem to be lacking. 25,26 Owing to their advantages, many researchers have suggested that halogenated furanone compounds would potentially be ideal antibacterial agents on implants for preventing biofilm infection.…”
Section: Introductionmentioning
confidence: 99%